How many times can the same story be told? - Vršič, Zarja (Stridon, 2025)
While existing scholarship on self-translation has primarily focused on interlingual transfers, this study aims to expand the concept to encompass intersemiotic and intrasemiotic translation by ex-amining how the French novelist and filmmaker Marguerite Duras reworked the themes of loss, death, and memory across both literature and film. Focusing on her “India Cycle” – a series of inter-related novels and films – this study explores and analyses Duras’s distinctive approach to repetition while emphasizing her personal motivations for continuously reinterpreting the same narratives across different artistic forms. Ultimately, this paper argues that Duras’s self-translation is not mere-ly a repetition of the same, but a creative process that generates new meanings in different contexts, reinforcing the cyclical and fragmented nature of her storytelling. Through this perspective, the India Cycle offers a compelling case for rethinking self-translation beyond linguistic boundaries, highlighting its broader implications for translation studies.
Keywords: Duras, Marguerite; India cycle; indijski cikel; intersemiotic translation; intrasemiotic translation; medznakovni prevod; samoprevajanje; self-translation; znotrajznakovni prevod